The 9th girl [compact disc, unabridged] - Hoag, Tami (Brilliance Audio, 2013)
The 9th Girl focuses on the ninth unidentified body to turn up in Minneapolis in 2012, nicknamed Jane Doe 9. When Kovac and Liska take on the case, they discover a shocking fact: This victim has been found without any identifiable characteristics, except for those that peg her as an adolescent girl. Before the investigation is through, the case will take the two detectives deep into the life and death of a teenage girl who wanted nothing more than to be 'normal.' They will come perilously close to the bullies who tormented her, the twisted family dynamics that may have contributed to her death, and ultimately to the haunting details of a young love that just may hide the secret of Jane Doe 9's terrible fate.